2012
DOI: 10.1007/s10818-012-9141-5
|View full text |Cite
|
Sign up to set email alerts
|

Is cooperation instinctive? Evidence from the response times in a public goods game

Abstract: In this work we use data on response times from a public good experiment to test the hypothesis that cooperation is instinctive, under the assumption that the longer the time of the decision, the less instinctive the choice. Results seem to support the hypothesis that cooperation is instinctive, while defection is 'rational'. Moreover, as the experiment is designed also to assess the effects of the consumption of relational goods on cooperation, we are also able to state that some types of relational goods, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
65
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 27 publications
13
65
1
Order By: Relevance
“…Consistent with experimental studies, which found that encouraging intuitive processing increased cooperation (Rand et al, 2014), several studies have reported a negative REACTION TIMES AND REFLECTION 7 correlation between reaction times and cooperation (Capellan et al, 2014;Lotito et al, 2013;Nielsen et al, 2014;Rand et al, 2012). However, counterexamples show that sometimes reaction times are positively correlated with cooperation.…”
Section: The Inverted-u Pattern Of Reaction Timessupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with experimental studies, which found that encouraging intuitive processing increased cooperation (Rand et al, 2014), several studies have reported a negative REACTION TIMES AND REFLECTION 7 correlation between reaction times and cooperation (Capellan et al, 2014;Lotito et al, 2013;Nielsen et al, 2014;Rand et al, 2012). However, counterexamples show that sometimes reaction times are positively correlated with cooperation.…”
Section: The Inverted-u Pattern Of Reaction Timessupporting
confidence: 53%
“…Previous studies have produced conflicting results as to whether reaction times are positively (Piovesan & Wengström, 2009) or negatively (Capellan et al, 2014Lotito et al, 2013;Nielsen et al, 2014;Rand et al, 2012) Although reaction times are sometimes interpreted as a veridical indicator of the degree of reflection, the pattern of reaction times observed in Studies 1-3 was different from the effects of experimentally manipulating intuitive or reflective processing. Forcing participants to respond intuitively through time pressure (Study 4) or cognitive priming (Study 6) decreased the rate of selfish decisions, had no effect on the rate of intermediate decisions, and increased the rate of cooperative decisions.…”
Section: Reaction Times and Reflection 28mentioning
confidence: 94%
“…Furthermore, individual differences in reaction times, which are often interpreted as a proxy for intuitiveness (although see refs. 45 and 46 for an alternative interpretation based on decision conflict), have been associated with both increased (4,(47)(48)(49) and decreased (50, 51) cooperation. Our model therefore helps to explain the otherwise-puzzling difference in experimental results between cognitive process manipulations and reaction time correlations.…”
Section: Discussionmentioning
confidence: 99%
“…They interpret this as evidence that giving is 'spontaneous' and greed 'calculated'. Similarly, Lotito et al (2013) report that lower decision times are associated with more cooperation in a public good game, and Nielsen et al (2013) find that free-riders, classified according to the Fischbacher et al (2001) taxonomy of contributor types, exhibit longer decision times than do conditional cooperators. Tinghög et al (2013), however, find no statistically significant effect of time-pressure in public good games, whereas Lohse et al (2014) report the opposite pattern-that decision times are positively correlated with contributions.…”
Section: Self-control and Social Dilemmasmentioning
confidence: 99%